2007
DOI: 10.1073/pnas.0605934104
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of cone precursors to functional rod photoreceptors by bZIP transcription factor NRL

Abstract: Networks of transcriptional regulatory proteins dictate specification of neural lineages from multipotent retinal progenitors. Rod photoreceptor differentiation requires the basic motifleucine zipper (bZIP) transcription factor NRL, because loss of Nrl in mice (Nrl ؊/؊ ) results in complete transformation of rods to functional cones. To examine the role of NRL in cell fate determination, we generated transgenic mice that express Nrl under the control of Crx promoter in postmitotic photoreceptor precursors of W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
155
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 138 publications
(166 citation statements)
references
References 64 publications
(74 reference statements)
11
155
0
Order By: Relevance
“…The inner neurons that ordinarily contact cones, such as ON cone bipolar and horizontal cells, make connections with rods in these mice. No cone-specific gene products were detected by RT-PCR or immunohistochemistry (Oh et al, 2007). Thus, Nrl is sufficient to guide photoreceptor precursors to a rod lineage.…”
Section: Animal Studiesmentioning
confidence: 85%
See 3 more Smart Citations
“…The inner neurons that ordinarily contact cones, such as ON cone bipolar and horizontal cells, make connections with rods in these mice. No cone-specific gene products were detected by RT-PCR or immunohistochemistry (Oh et al, 2007). Thus, Nrl is sufficient to guide photoreceptor precursors to a rod lineage.…”
Section: Animal Studiesmentioning
confidence: 85%
“…However, conditional expression of Nrl later during S-cone differentiation, using the S-cone promoter on the Nrl −/− background, generated hybrid cells that co-expressed both rhodopsin and S-opsin. Although lineage-tracing experiments showed that some of the S-cones might have switched to a rod lineage, no rod function was detected by ERG in these mice (Oh et al, 2007), suggesting that differentiated photoreceptors may have limited plasticity, but require appropriate transcriptional regulation for maintenance. Another possible explanation, however, is that Nrl represses expression of S-cone genes, resulting in inactivation of cells already committed to the S-cone lineage.…”
Section: Animal Studiesmentioning
confidence: 90%
See 2 more Smart Citations
“…Nrl induces Nr2e3 expression and these two genes define a transcriptional hierarchy for rod differentiation. Nrl Ϫ/Ϫ mice overproduce S cones at the expense of rods (6) whereas ectopic Nrl expression converts cones to rods (14). Nr2e3 deficiency causes an enhanced cone phenotype and misexpression of cone genes in rods, suggesting that Nr2e3 represses cone genes to maintain the rod phenotype (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%